The impact of gas physics on strong cluster lensing - Puchwein, Ewald; Bartelmann, Matthias; Meneghetti, Massimo (Arxiv, 2014)
Previous studies of strong gravitational lensing by galaxy clusters neglected the potential impact of the intracluster gas. Here, we compare simulations of strong cluster lensing including gas physics at increasing levels of complexity, i.e. with adiabatic, cooling, star-forming, feedback-receiving, and thermally conducting gas, and with different implementations of the artificial viscosity in the SPH simulations. Each cluster was simulated starting from the same initial conditions such as to allow directly comparing the simulated clusters. We compare the clusters' shapes, dynamics and density profiles and study their strong-lensing cross sections computed by means of ray-tracing simulations. We find that the impact of adiabatic gas depends on the amount of turbulence that builds up, which means that the artificial viscosity plays an important role. With the common viscosity implementation, adiabatic gas has little effect on strong cluster lensing, while lower viscosity allows stronger turbulence, thus higher non-thermal pressure and a generally broader gas distribution which tends to lower lensing cross sections. Conversely, cooling and star formation steepen the core density profiles and can thus increase the strong-lensing efficiency considerably.
Gesehen am 26.09.2017